Presenting a Content Marketing Process Model in the Iranian Banking Industry (Case Study: Bank Mellat) - Soleymani , Mahdi; Rousta, Alireza; Asayesh , Farzad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: This study aims to identify the critical components and strategies that can enhance the effectiveness of content marketing efforts, thereby improving market share and customer engagement. Methodology: This study adopts a qualitative research approach, utilizing grounded theory to construct a process model for content marketing. It involves semi-structured interviews with a purposively selected group of 15 experts, including academic scholars and banking industry professionals, to ensure a deep understanding of the subject matter. The data analysis proceeded through open, axial, and selective coding, leading to the identification of main categories, axial categories, and concepts. Findings: The research identifies several main categories critical for the successful implementation of content marketing in the banking sector. These include business understanding and planning, creation of a content management and strategy unit, setting content marketing goals, understanding audiences, identifying audience needs, determining content idea and theme, content production management, content publication management, managing expectations and customer experience, and feedback collection and process improvement. Each category encompasses various sub-categories and concepts, outlining a detailed framework for effective content marketing strategies. Conclusion: The study concludes that a structured approach to content marketing, encompassing a thorough understanding of business objectives, audience needs, and the strategic planning of content creation and distribution, is crucial for enhancing the banking industry’s market share and customer satisfaction. The proposed model offers a comprehensive guideline for banks to refine their content marketing efforts, suggesting that a focus on audience engagement, content relevancy, and continuous improvement based on feedback can significantly impact marketing success. The findings imply that adopting this model can help banks achieve a competitive edge through targeted, effective content marketing strategies.